The Imbibition of Pea (Pisum sativum L.) Seeds in Silver Nitrate Reduces Seed Germination, Seedlings Development and Their Metabolic Profile - Joanna Szablińska-Piernik; Lesław Bernard Lahuta; Karolina Stałanowska; Marcin Horbowicz (Plants, 2022)
The use of silver nanoparticles (Ag NPs) on plants is accompanied by the occurrence of Ag+ ions, so the research of the effects of both on plants should be related. Therefore, in our study, the effects of Ag NPs suspension (containing Ag0 at 20 mg/L) and AgNO3 solutions (with the concentration of Ag+ ions at 20 and 50 mg/L) on the seed germination and early seedling growth (4 days) of pea (Pisum sativum L.) were compared. Both Ag NPs and AgNO3 did not decrease seed germination, and even stimulated seedling growth. In seedlings developing in the Ag NPs suspension, an increase in monosaccharides, homoserine and malate was noted. In the next experiment, the effect of short-term seed imbibition (8 h) in AgNO3 at elevated concentrations, ranging from 100 to 1000 mg/L, on the further seed germination, seedling growth (in absence of AgNO3) and their polar metabolic profiles were evaluated. The seed imbibition in AgNO3 solutions at 500 and 1000 mg/L reduced seed germination, inhibited seedlings’ growth and caused morphological deformations (twisting and folding of root). The above phytotoxic effects were accompanied by changes in amino acids and soluble carbohydrates profiles, in both sprouts and cotyledons. In deformed sprouts, the content of homoserine and asparagine (major amino acids) decreased, while alanine, glutamic acid, glutamine, proline, GABA (γ-aminobutyric acid) and sucrose increased. The increase in sucrose coincided with a decrease in glucose and fructose. Sprouts, but not cotyledons, also accumulated malic acid and phosphoric acid. Additionally, cotyledons developed from seeds imbibed with AgNO3 contained raffinose and stachyose, which were not detectable in sprouts and cotyledons of control seedlings. The obtained results suggest the possible disturbances in the mobilization of primary (oligosaccharides) and presumably major storage materials (starch, proteins) as well as in the primary metabolism of developing seedlings.